Analysis of Existing Approaches to Constructing Component-based Systems Directly from Natural Language Requirements - Nordin, Azlin (2012)
System development generally starts with Requirements Engineering (RE) process. Based on requirements, system analysts produce the requirements documents and analyze them in order to produce design documents. These artefacts will be inputs to the later stages in the system development. It is argued that during the transition between these stages, considering many other various factors, information might be missed out or misinterpreted along the way. Hence, a better transition in the development cycle is required. This paper outlines and provides an analysis of the existing approaches in the literature on constructing systems from natural language requirements (NLR) as to provide the motivation of a new approach to constructing component-based system from NLR.